The Influence of Competence and Professionalism on Performance Auditor at the Sumedang Regency Inspectorate - Azis Nurkholik; Erpi Rahman; Gunawan Wibisana (LPPM Universitas Sebelas April, 2021)
The less than optimal performance of the auditors is thought to be caused by poor competence and professionalism of the auditors. This study aims to determine the effect of Competence and Professionalism on Auditor Performance. The Independent Variables used in examining the Auditor's Performance include Competence and Professionalism. This study uses survey methods, data collection techniques used are observation, interviews, literature studies, questionnaires and data processing. The sampling technique in this study used a purposive sample, while the data sources were primary and secondary data types. The data analysis was carried out with validity tests, normality tests, reliability tests, multiple linear regression analysis tests, correlation coefficient analysis tests, determination tests, and hypothesis testing using the SPSS version 25 program. The results of this study were the coefficient of determination, the magnitude of the influence of Competence (X1) Professionalism (X2) on Auditor Performance (Y) can be seen from the coefficient of determination (R2) obtained by 0.858 or 85.8%. So Competence (X1) and Professionalism (X2) have an influence on Auditor Performance (Y) by 85.8%. While 100%-85.8% = 14.2% other influenced by other factors that are not included in the variables of this study. This means that the higher the competence and professionalism, the better the auditor's performance will be. While the results of statistical testing of the F test based on the Anova table show Fcount 60.627 > Ftable 3.47 and a significance value of 0.000 <0.005. So on this basis Ha is accepted and Ho is rejected. This states that there is a positive and significant influence of Competence and Professionalism together on the Performance of Auditors at the Sumedang Regency Inspectorate. In the Coefficient of Determination, the regression (R) is 0.927 and R Square (R2) is 0.859. This means that the variables of Competence and Professionalism affect the audit quality variable by R2 or 85.9% while the remaining 14.1% is influenced by other factors that are not included in this research variable.